Comprehensive RF safety concept for parallel transmission MR. Issue 2 (22nd August 2014) - Graesslin, Ingmar; Vernickel, Peter; Börnert, Peter; Nehrke, Kay; Mens, Giel; Harvey, Paul; Katscher, Ulrich
<x xml:space="preserve">Abstract</x> Purpose The goal of this study is to increase patient safety in parallel transmission (pTx) MRI systems. A major concern in these systems is radiofrequency‐induced tissue heating, which can be avoided by specific absorption rate (SAR) prediction and SAR monitoring before and during the scan. Methods In this novel comprehensive safety concept, the SAR is predicted prior to the scan based on precalculated fields obtained from electromagnetic simulations on different body models. The radiofrequency fields and the global and local SAR are supervised in real time during the scan. This concept is integrated into a 3 T pTx MR scanner and validated experimentally. Results Phantom and in vivo experiments successfully validated the basic feasibility of the real‐time SAR supervision concept. Supervising the SAR minimizes SAR overestimation. Monitoring the radiofrequency fields allows the detection of unsafe radiofrequency situations for the patient, which a SAR supervision system alone cannot detect. Conclusion This study demonstrates safe scanning in a pTx system. This new safety concept is also applicable for field strengths above 3 T and represents an important step toward safe operation of pTx systems. Magn Reson Med 74:589–598, 2015. © 2014 Wiley Periodicals, Inc.